Academic help-seeking behaviour and barriers among college nursing students - Million S. Bimerew; John P. Arendse (AOSIS, 2024)
Background: First-year college student's smooth transition and academic success influenced by academic help-seeking behaviour. Academic help-seeking behaviour is largely affected by many factors, including demographic factors, self-esteem and the use of sources for academic learning. Aim: The study investigated academic help-seeking behaviour and barriers among first-year college nursing students. Setting: The study was conducted at a nursing college in the Western Cape province of South Africa. Methods: A cross-sectional descriptive survey design with a self-administered questionnaire was used to collect data from 130 first year nursing college students. Descriptive statistics and bivariate analysis were computed using Statistical Packages for Social Sciences (SPSS). Results: More than 77.7% used course materials and books to help with academic learning, 50% of students sought help from their teachers. Only 24.6% and 17.7% of students used YouTube and computers respectively. In all items measured help-seeking is not a threat to self-esteem, teachers and parents did not have unrealistic expectations of their academic performance. Language is significantly associated with (p  0.001) academic help-seeking behaviour. Conclusion: Most students mainly used informal sources for academic learning. Help-seeking was not a threat to self-esteem. The language barrier is significantly associated with academic help-seeking behaviour. The nursing college should provide a coordinated academic language support, academic consultation and counselling services for academically stressed first-year nursing students. Contribution: The findings highlighted language as a barrier to academic help-seeking. The study provides insight to strengthen the language and academic support for academic learning for first year nursing students.